Tertiary Students' ICT Selfefficacy Beliefs and the Factors Affecting Their ICT-Use - Turel, Vehbi; Calik, Sinan; Doganer, Adem (Igi Global, 2015)
This study looked at tertiary (i.e. undergraduate /a four-year degree) students' information and communication technology (ICT) self-efficacy beliefs and their level in use of certain common programmes at a newly established (i. e. 2007) university in Turkey in the spring of 2012. The study examined the tertiary students' (a) demographic background, (b) their ICT self-efficacy beliefs and (c) their ICT-using level in certain common programs. The students at three different departments were given the questionnaires to complete. 363 participants completed them. The study was mostly quantitative and partly qualitative. The quantitative results were analysed with SPSS (i. e. descriptive statistics, ANOVA, Independent Samples Test). The qualitative data were analysed by examining the participants' responses gathered from the open-ended questions and focussing on the shared themes among the responses. The results revealed that the participants were ICT literate and users. They had positive ICT self-efficacy beliefs and their level in certain programs was good. There were also statistical differences between (a) their ICT self-efficacy beliefs and (b) ICT level in certain common programs in terms of different independent variables (i. e. the length of ICT-use, the place of ICT-access, the frequency of ICT-use, the type of the course they were attending, and gender). The findings are consistent with models and theories of technology engagement which recognise facilitating or inhibiting conditions. The implications are (1) to provide (free) full-access to ICT in terms of efficient resources and technology availability, (2) to provide (efficient) ICT courses and (3) to integrate ICT into teaching/ learning.
Keywords: Facilitating or Inhibiting Conditions; Information and Communication Technology (ICT); ICT Self-Efficacy Beliefs; Tertiary Level; Undergraduate Students